Malaria in Pregnancy in Endemic Regions of Colombia: High Frequency of Asymptomatic and Peri-Urban Infections in Pregnant Women with Malaria - Ana-María Vásquez; Lina Zuluaga-Idárraga; Margarita Arboleda; Luz-Yáned Usuga; Carolina Gallego-Marin; Alvaro Lasso; Luisa Carbal; Juan-Gabriel P; Alberto Tobón-Castaño (Hindawi Limited, 2020)
Background. Malaria in pregnancy (MiP) has been associated with adverse pregnancy outcomes. There is limited information on MiP in low transmission regions as Colombia. This study aimed to describe the epidemiology of MiP through active surveillance of infections by microscopy and polymerase chain reaction (PCR). Methods. A cross-sectional study was conducted between May 2016 and January 2017 in five municipalities (Apartadó, Turbo, El Bagre, Quibdó, and Tumaco) in Colombia. Pregnant women self-presenting at health centers for antenatal care visits, seeking medical care for suspected malaria, or delivery, were enrolled. Diagnosis of Plasmodium spp was made in peripheral and placental blood samples by microscopy and PCR. Results. A total of 787 pregnant women were enrolled; plasmodial infection was diagnosed by microscopy in 4.2% (95% CI 2.8-5.6; 33/787) or by nPCR in 5.3% (95% CI 3.8-6.9; 42/787) in peripheral blood. Most of the infections were caused by P. falciparum (78.5%), and 46% were afebrile (asymptomatic). Women in the first and second trimester of pregnancy were more likely to be infected (aOR=3.06, 95%CI=1.6−5.8). To live in the urban/peri-urban area (aOR=3.04, 95%CI=1.4−6.56), to have a history of malaria during last year (aOR=5.45, 95%IC=2.16−13.75), and the infrequent bed net usage (aOR=2.8, 95%CI=1.31−5.97) were associated with the infection. Pregnant infected women had a higher risk of anaemia (aOR=2.18, 95%CI=1.15−4.12) and fever (aOR=14.2, 95%CI=6.89−29.8). Conclusion. The screening for malaria during antenatal care in endemic areas of Colombia is highly recommended due to the potential adverse effects of Plasmodium spp. infection in pregnancy and as an important activity for the surveillance of asymptomatic infections in the control of malaria.